ChemInform Abstract: An Improved Suzuki—Miyaura Cross‐Coupling Reaction with the Aid of in situ Generated PdNPs: Evidence for Enhancing Effect with Biphasic System. Issue 46 (October 2016) - Mahanta, Abhijit; Mondal, Manoj; Thakur, Ashim Jyoti; Bora, Utpal
Abstract: An improved procedure for the Suzuki—Miyaura cross‐coupling in a water extract of rice straw ash is presented.